Preceding deformation effects on the crush response of the circular cup - Mohd Amman, Rosmia (UTeM, 2018)
Automotive body structure is made up of formed components which have undergone plastic deformation during forming process that altered the structural behaviour of these components. Ignoring the preceding deformation effects in subsequent crush analysis could lead to inaccurate crashworthiness evaluation. In this study, the crush response of circular cup has been studied to quantify the effects of neglecting the preceding deformation effects such as geometrical changes and work hardening effects. The draw formed circular cups were fabricated through draw forming experiment on advanced high strength steel, dual-phase (DP600) steel with a nominal sheet thickness of 1.2 mm. Quasi-static crush experiment was subsequently performed on the draw formed circular cup to examine the preceding deformation effects on crush response. The draw forming simulation was performed at various punch speeds to investigate the geometrical changes and strain rates effect on deformation behaviour. An ideal computer-aided design (CAD) and draw formed cup model were used to developed finite element (FE) crush models in order to investigate the effects of geometrical changes and work hardening incurred during the draw forming process. The measured global load-displacement curve from experiments were used to validate the FE models developed using HyperWork. All draw forming and quasi-static crush experiments were simulated using Radioss solver employing Johnson-Cook constitutive model with isotropic hardening rule. The subsequent crush simulation was performed with and without incorporating mapped contour. Results show that draw forming process at various punch speeds affected the material strength and deformation behaviour of draw formed circular cup. In case of crush simulation without mapping (case A and case B), the geometrical changes from preceding draw forming process greatly affected the crush response of circular cup. The maximum force recorded at the end of crush process led to 46% and 15.2% higher for ideal CAD and draw formed cup geometry, respectively compared to the experiment. While in the case of with mapping (case 1 and case 2), work hardening effect resulted from draw forming process overcame the thinning effect and therefore made the structure stiffer and led to higher force value when compared to the case of without mapping. The percentage difference of maximum load recorded at the end of crush analysis with and without mapped residual contour was 12.9% and 3.8% for ideal CAD and draw formed cup model, respectively. Dynamic crush event showed higher response compared to quasi-static crush event in terms of load-displacement, stress and energy absorption behaviour by 45.5%, 40.7% and 30.7% respectively due to strain rates and inertia effects. Based on the crush response of the circular cup, the preceding deformation effects should be included in subsequent crush analysis by mapping the residual contour on draw formed geometry, instead on ideal CAD geometry in order to improve crashworthiness prediction.